Compassionate Leadership for School Belonging - Riley, Kathryn (UCL Press, 2022)
In Compassionate Leadership for School Belonging, international scholar and practitioner Kathryn Riley shines the powerful lens of belonging on schools. Belonging is that sense of being somewhere you can be confident you will fit in and feel safe in your identity: a feeling of being at home in a place. When belonging is a school's guiding principle more young people at all levels experience a sense of connectedness and friendship, perform better academically, and come to believe in themselves; their teachers feel more professionally fulfilled, their families more accepted. The originality of this highly readable book lies in its scope. It offers international analysis from the OECD, alongside insights from the author's extensive research in schools, powerfully supported by observational vignettes and drawings from the children, young people and teachers who have been her co-researchers. This exploration is supported by methodologies, concepts and research tools for use by practitioners, researchers and school leaders. While contemporary patterns of dislocation, disaffection and exclusion are revealed, the spotlight is firmly on what needs to change and how: the purposeful actions in classrooms and schools; the approaches at system level; and the compassionate forms of leadership that can help create the conditions for school belonging. In an increasingly uncertain world, this is an urgent book of hope and possibilities.